2003
DOI: 10.1002/jbm.a.20001
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases MMP‐2, ‐9 and tissue inhibitors TIMP‐1, ‐2 expression and secretion by primary human osteoblast cells in response to titanium, zirconia, and alumina ceramics

Abstract: Osteogenic properties of bone cells are a key parameter governing osseointegration of implant devices. In this context, osteoblasts have a central role via extracellular matrix synthesis and remodeling that they regulate through different protease activity. In this study, we have analyzed the expression of two matrix metalloproteinases (MMPs): MMP-2 (72 kDa) and MMP-9 (92 kDa) and their specific tissue inhibitors TIMP-1 and TIMP-2 in primary human osteoblastic cells. The effect of titanium, zirconia, and alumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 44 publications
0
17
0
2
Order By: Relevance
“…Extracellular matrix degrading MMPs, secreted by osteoblasts, have been reported to be involved in physiologic and pathological bone remodeling. MMP‐1, ‐2, ‐3, and ‐13 have been suggested to play a role in physiologic bone remodeling,8, 9, 12 MMP‐13 in fracture healing22, and MMP‐2 and MMP‐9 in foreign body reaction relating to periprosthetic osteolysis 23, 24. This study showed that uniaxial cyclic stretching transiently upregulated the expression of MMP‐1 and MMP‐3 in normal human osteoblasts cultured on collagen gels.…”
Section: Discussionmentioning
confidence: 58%
“…Extracellular matrix degrading MMPs, secreted by osteoblasts, have been reported to be involved in physiologic and pathological bone remodeling. MMP‐1, ‐2, ‐3, and ‐13 have been suggested to play a role in physiologic bone remodeling,8, 9, 12 MMP‐13 in fracture healing22, and MMP‐2 and MMP‐9 in foreign body reaction relating to periprosthetic osteolysis 23, 24. This study showed that uniaxial cyclic stretching transiently upregulated the expression of MMP‐1 and MMP‐3 in normal human osteoblasts cultured on collagen gels.…”
Section: Discussionmentioning
confidence: 58%
“…Besides, we found that there was no significant secretion of MMP2 and 9 in both cell lines and time intervals due to ZnO NP and ZnCl 2 treatments. It was considered that MMPs as zinc-dependent endopeptidases play crucial roles in tumor invasion, morphogenesis, angiogenesis, metastasis, and wound healing by remodelling of extracellular matrix (Murphy et al 1994;Parsons et al 1997;Oum'hamed et al 2004). These data suggested lack of early acquisition of cancer markers upon ZnO NP and ZnCl 2 chronic exposures after chronic exposures despite the fact that vulnerable MEF Ogg1 gene knockout cell line was used.…”
Section: Figmentioning
confidence: 88%
“…Boyan et al 46) demonstrated that rough surface may enhance osteoblasts differentiation, and fine-tuning of the biomaterial surface topography may also possible control intracellular signaling events 47) . Oum'hamed et al 48) and Carinci et al 10) showed in their studies that zirconia, alumina, and titanium are able to upregulate or downregulate the expression of some genes and proteinases. We presume that the higher ALP expression of NANOZR maybe ascribes to its unique intergranular-type nanostructure, and ceria and alumina in NANOZR may also affect the osteoblast differentiation.…”
Section: Discussionmentioning
confidence: 99%